1989
DOI: 10.1177/000992288902801007
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides, Cholesterol, HDL, LDL, and VLDL Cholesterol in Serum of Phenylketonuric Children Under Dietary Control

Abstract: Phenylketonuria is currently treated by a special diet to avoid elevated blood concentration of the essential amino acid phenylalanine. The authors examined 20 phenylketonuric children in the Inborn Error of Metabolism Department of Institute of Child Health in Athens. The children had simultaneous clinical and laboratory investigations. Blood cholesterol levels of these children were low in comparison with the levels of healthy children of the same age, but the triglyceride levels were higher as a result of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
0
18
2
Order By: Relevance
“…Following the recommendation to analyze the absolute data used in the MetSyn definition, together with other biomarkers [15], we could not only substantiate the reductions in total cholesterol concentrations [41,42], but also found statistical significant lower glucose concentrations notwithstanding the sugar-rich dietary pattern without increased insulin secretion. The exact clinically significance of this finding needs to be elucidated.…”
Section: Discussionmentioning
confidence: 70%
“…Following the recommendation to analyze the absolute data used in the MetSyn definition, together with other biomarkers [15], we could not only substantiate the reductions in total cholesterol concentrations [41,42], but also found statistical significant lower glucose concentrations notwithstanding the sugar-rich dietary pattern without increased insulin secretion. The exact clinically significance of this finding needs to be elucidated.…”
Section: Discussionmentioning
confidence: 70%
“…To support this hypothesis, previously published studies have suggested a similar or even improved lipid profile in PKU children compared to healthy controls [25]. Only few studies have explored lipid profile or other coronary heart disease-related parameters in PKU patients.…”
Section: Discussionmentioning
confidence: 98%
“…These findings have been explained by a high polyunsaturated=saturated fatty acid ratio (P:S), low dietary fat and cholesterol intake, high fibre intake and primarilly plant protein sources (Pan Wen Ham et al, 1993). In this respect PKU children on diet can be considered vegetarians (Schulpis & Scarpalezou, 1988). However, not all the patients adhere to the recommended diet.…”
Section: Discussionmentioning
confidence: 99%